Responses of triacylglycerol synthesis in Skeletonema marinoi to nitrogen and phosphate starvations. Issue 6 (11th August 2020) - Zhang, Mei; Xing, Yongze; Wang, Fuwen; Mi, Tiezhu; Zhen, Yu
Abstract : Skeletonema marinoi is one of the most widespread marine planktonic diatoms in temperate coastal regions and sometimes can form massive blooms. Yet, the molecular mechanisms of triacylglycerol (TAG) synthesis in nutrient‐deficient conditions for this species are still unknown. This study aimed to investigate how the TAG biosynthetic pathway of S. marinoi reacts to the culture age and nitrogen (N) or phosphorus (P) deficiency at molecular levels. Meanwhile, we also described the physiological and biochemical changes of S. marinoi in response to N or P starvation over time. To obtain reliable qRT‐PCR data, six putative reference genes were identified for assessing expression stability using geNorm and BestKeeper software, and Actin exhibited the most stable expression across 45 tested S . marinoi samples. We found that the expression of TAG biosynthesis‐related genes and ACCase enzyme activity varied in response to the different nutrient conditions and culture age. Taken together, we speculated that the capacity of TAG biosynthesis in S. marinoi is induced by N or P stress, and increases with culture age. Furthermore, TAG biosynthesis appears to respond more strongly to P deficiency than to N deficiency. Our study provides important insights into how diatoms regulate the TAG biosynthetic pathway when stressed by nutrient limitation. Besides, the data obtained from this study also provide useful clues for further exploring genes that can be used for metabolic engineering to enhance lipid production.